Dissenting from care.data: an analysis of opt-out forms - Vezyridis, Paraskevas; Timmons, Stephen (BMJ Publishing Group Ltd, 2016)
Background Care.data was a programme of work led by NHS England for the extraction of patient-identifiable and coded information from general practitioner GP records for secondary uses. This study analyses the forms (on the websites of GP practices) which enabled patients to opt out. Methods Theoretical sampling and summative content analysis were used to collect and analyse dissent forms used by patients to opt out from care.data. Domains included basic information about the programme, types of objections and personal details required for identification purposes. Results One hundred opt out forms were analysed. Fifty-four forms mentioned that this programme was run by NHS England. Eighty-one forms provided 2 types of objections to data sharing and 15 provided only one objection. Only 26 forms mentioned that direct care would not be affected and 32 that patients maintain their right to opt back in anytime. All but one of the opt out forms we reviewed requested the name of the person wishing to opt out. Ninety-four required a date of birth and 33 an NHS number. Eighty-two required an address, 42 a telephone number and 7 an email address. Conclusion Numbers of patients (not) opting out should be treated with caution because the variability of information provided and the varied options for dissent may have caused confusion among patients. To ensure that dissent is in accordance with individual preferences and moral values, we recommend that well-designed information material and standardised opt out forms be developed for such data sharing initiatives.